Pengaruh Struktur Kepemilikan Institusional Dan Financial Leverage Terhadap Manajemen Laba - Titania Ayudia; Nesti Hapsari (COSTING : Journal of Economic, Business and Accounting, 2021)
This study aims to determine whether there is an influence of Institutional Ownership Structure, Debt to Equity Ratio, and Debt to Asset Ratio to the Earnings Management partially or jointly. The method used in this research is descriptive method verification with a quantitative approach sourced from the annual financial statements on manufacturing companies sub sector of food and beverage, and literature studies. The sampling technique uses non probability sampling with purposive sampling technique. The data obtained were analyzed by testing the classic assumption, multiple linear regression analysis and hypothesis testing using t test and f test. This study uses the SPSS version 26 program to process data. The results of this study indicate that, Institutional Ownership Structure does not affect the Earnings Management, Debt to Equity Ratio (DER) have a negative and significant effect the Earnings Management, Debt to Asset Ratio (DAR) have a positive and significant effect the Earnings Management. And simultaneously Institutional Ownership Structure, Debt to Equity Ratio, and Debt to Asset Ratio have a affect the Earnings Management. Keyword : Institutional Ownership Structure, Debt to Equity Ratio (DER), Debt to Asset Ratio (DAR), and Earnings Management.